Heterogeneous hydroxypropylation for the preparation of hydroxypropyl carrageenan and its application in Plant-Based hard capsules - Zi-Yun Zhou; Mi Zhang; Yu-Cheng Yang; Pei-Yong Liu; Yi Chen; Bing-De Zheng; Na Zhang; Xue-Qin Zhang; Jing Ye; Mei-Tian Xiao (Carbohydrate Polymer Technologies and Applications)
Plant-based hard capsules hold promise as medicinal excipients; however, the widely used gelling agent κ-carrageenan (κ-C) suffers from limitations such as poor aqueous solubility, and high dissolution temperature, which hinder the dissolution performance of the capsules. To overcome these drawbacks, we employed an industrially scalable heterogeneous hydroxypropylation method to modify κ-C. This process involves adjusting reaction parameters, including ethanol concentration, alkalization conditions and etherification conditions, to optimize the molar substitution degree (MS) and gel strength of the resulting hydroxypropylated carrageenan (HPC). Structural analysis using techniques such as FTIR spectroscopy, 1HNMR spectra and 13C NMR spectra confirmed the incorporation of hydroxypropyl groups into the κ-C backbone. Kinetic studies revealed that the hydroxypropylation reaction follows second-order kinetics with respect to propylene oxide, with an activation energy of 47.51 kJ/mol. Compared to κ-C, HPC exhibits improved water solubility, dissolving readily at lower temperatures, and demonstrates a lower gel-sol transition temperature, which facilitates easier processing. Tests show that capsules made from HPC exhibit a faster disintegration rate in pH 6.8 phosphate buffer compared to those made from κ-C and demonstrate an enhanced dissolution profile. These findings demonstrate a promising strategy to address the intrinsic limitations of κ-C and advance the development of plant-based hard capsules.